PENGARUH PERAN ORANG TUA DAN KESIAPAN BELAJAR TERHADAP PRESTASI BELAJAR IPA - Irani Lailatul Badria; Dyah Ayu Fajarianingtyas; Henny Diana Wati (LENSA (Lentera Sains): Jurnal Pendidikan IPA, 2018)
The aimed of this research is 1) to know the influence of parent's role to the learning achievement of science class VII SMPN 2 Saronggi, 2) to know the influence of learning readiness to science achievement of grade VII students SMPN 2 Saronggi and 3) to know the influence of parent role to Readiness of students of grade VII SMPN 2 Saronggi. Data collection  parent role, readiness of study with questionnaire and learning achievement with documentation study. Data analysis technique used in this research is Structural Equation Model (SEM). The result of this research is 1) there is no influence of parent's role to the achievement of science learning grade VII SMPN 2 Saronggi, because P-value> 0,05 is 0,807, 2) there is influence of readiness study to science achievement of student of class VII SMPN 2 Saronggi Because the value of P-value (0,032) <0,05 and 3) there is no influence of parent role to readiness of student of class VII SMPN 2 Saronggi because value of P-value (0,317)> 0,05. Readiness to learn affect the learning achievement of science class VII SMPN 2 Saronggiurus parent role does not affect the learning achievement and readiness to study class VII SMPN 2 Saronggi.